Translating translanguaging into our classrooms: Possibilities and challenges - Oliver, Rhonda; Wigglesworth, G.; Angelo, D.; Steele, Carly (SAGE PUBLICATIONS LTD, 2021)
With a focus on Australian Aboriginal students, in this article we argue that translanguaging provides a useful resource for multilingual learners. We point out that although translanguaging is a relatively recent term, in Indigenous Australia is has been used consistently throughout the ages as people from different languages communicated with each other. We argue that through the use of translanguaging in the classroom, children can be supported to draw on the wide range of linguistic resources they bring with them to school. Using data collected from an Aboriginal school in the Northern Territory and one in Western Australia, we illustrate the ways in which this perspective can inform approaches to teaching which will both enhance these learners’ communication skills in Standard Australian English (SAE) in the classroom, and, importantly, at the same time demonstrate that the languages the children come to school with are valued.